2016
DOI: 10.3855/jidc.6697
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of risk factors for carbapenem-resistant Klebsiella pneumoniae acquisition among ICU patients

Abstract: Introduction: Carbapenem-resistant Klebsiella pneumoniae (CRKP) is rapidly emerging as a life-threatening nosocomial infection. In this study, we aim to identify risk factors, especially antibiotic use, for CRKP infection among intensive care unit (ICU) patients. Methodology: This was a matched case-control study of a 67-bed ICU in a tertiary care teaching hospital from 1 January 2011 through 30 June 2013. The control cases were selected among the patients with carbapenem-susceptible Klebsiella pneumoniae (CSK… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 29 publications
10
21
0
Order By: Relevance
“…In our study, previous exposure to carbapenems predisposed patients for HIs caused by CR-Kp by 7.0-fold (95% CI=1.054-46.572; p=0.044) consistent with the results of previous studies (17,18). According to the case-control study by Wu and associates (14), an independent risk factor for contracting CP-Kp infection is the previous use of carbapenems (OR=12.69, 95% CI=2.09-77.10; p=0.006).…”
Section: Discussionsupporting
confidence: 92%
“…In our study, previous exposure to carbapenems predisposed patients for HIs caused by CR-Kp by 7.0-fold (95% CI=1.054-46.572; p=0.044) consistent with the results of previous studies (17,18). According to the case-control study by Wu and associates (14), an independent risk factor for contracting CP-Kp infection is the previous use of carbapenems (OR=12.69, 95% CI=2.09-77.10; p=0.006).…”
Section: Discussionsupporting
confidence: 92%
“…Although the CRE prevalence in Thailand remains low (<5%), the rate of CRE detection has been rising over time . The increasing rate of CRE in hospitals has been affected by various factors . One important reason for the recent spread and development of antibiotic resistance is antimicrobial consumption.…”
Section: What Is Known and Objectivementioning
confidence: 99%
“…3,6,7 The increasing rate of CRE in hospitals has been affected by various factors. [8][9][10][11][12] One important reason for the recent spread and development of antibiotic resistance is antimicrobial consumption. Numerous studies have demonstrated that an increasing rate of antimicrobial usage is associated with a rising incidence of bacterial resistance.…”
Section: What Is K Nown and Objec Tivementioning
confidence: 99%
“…The rising incidence of resistant strains may be due to high antibiotic exposure. Antibiotic exposure could be identified as a risk factor for emerging resistance in gram-negative bacteria in other settings [10]. The antibiotic exposure after kidney transplantation is elevated due to treatment of asymptomatic bacteriuria (ASB) and pneumocystis pneumonia (PCP) prophylaxis.…”
Section: Introductionmentioning
confidence: 99%